How does perceived heat stress differ between urban forms and human vulnerability profiles? Case study Berlin - N. Iqbal; M. Ravan; Z. Mitraka; J. Birkmann; S. Grimmond; D. Hertwig; N. Chrysoulakis; G. Somarakis; A. Wendnagel-Beck; E. Panagiotakis (Natural Hazards and Earth System Sciences)
Urban areas in all world regions are experiencing increasing heat stress and heat-related risks. While in-depth knowledge exists in terms of the urban heat island effect and increased heat stress in cities in the context of climate change, less is known about how individual heat perceptions and experiences differ between urban forms or with different vulnerability profiles of exposed people. It is crucial to identify and assess differences within cities relating to urban form and social structure, as both need to be considered when designing adaptation plans for heat-related risks. Here, we explore linkages between urban structure types (USTs), heat stress perception and different socio-economic groups' experiences in Berlin using a household survey, statistical and earth observation data. Our approach (1) quantifies perceived heat stress across USTs, considering characteristics such as, age, income, vegetation cover and shade, (2) characterises social dimensions of USTs to enhance their application in climate adaptation and (3) benefits from the synergistic disciplinary approach of the urbisphere project with rich social and physical datasets. Although heat stress exposure is higher in the inner-city ring, we find that a higher percentage of vulnerable groups in the outer city (6 to 18 km from the city centre), where 78 % of Berlin's elderly live. We underscore the need for attention in future adaptation plans based on the USTs, human vulnerability profile and adaptive capacities. For example, in densely spaced building blocks 67 % of respondents perceived high heat stress and fractions of vegetation and shade are comparatively very low. The method and findings can inform future adaptation strategies of other cities to consider different profiles of vulnerability and adaptive capacities within and between USTs.